Method for producing extruded styrene resin foam

By adding a polyhydric alcohol fatty acid ester to the graphite masterbatch in styrene-based resin extruded foam production, the issue of foreign matter generation is addressed, resulting in improved foam quality and consistency.

JP7663382B2Active Publication Date: 2025-04-16KANEKA CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021046521
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-19
Publication Date
2025-04-16
Estimated Expiration
2041-03-19

AI Technical Summary

Technical Problem

The generation of foreign matter in styrene-based resin extruded foams occurs when graphite is added in the form of a masterbatch, affecting the quality and consistency of the foam.

Method used

Incorporating a polyhydric alcohol fatty acid ester into the graphite masterbatch adjusts the melt mass flow rate (MFR) and improves the kneadability of the styrene resin and graphite masterbatch, thereby suppressing the generation of foreign matter.

Benefits of technology

The method effectively stabilizes the production of styrene-based resin extruded foams by reducing foreign matter generation, ensuring consistent quality and improved processing characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663382000001
    Figure 0007663382000001
  • Figure 0007663382000002
    Figure 0007663382000002
Patent Text Reader

Abstract

To provide a method for manufacturing a styrenic resin extruded foam which suppresses occurrence of a foreign matter.SOLUTION: A method for manufacturing a styrenic resin extruded foam includes a step of melting and kneading a styrenic resin, a graphite masterbatch and a foaming agent, wherein the graphite masterbatch contains graphite and a polyhydric alcohol fatty acid ester.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an extruded styrene resin foam. [Background technology]

[0002] Extruded styrene resin foams are generally produced continuously by heating and melting a styrene resin composition using an extruder or the like, then adding a blowing agent under high pressure conditions, cooling to a predetermined resin temperature, and then extruding the resulting mixture into a low pressure region.

[0003] Due to their excellent workability and heat insulating properties, extruded styrene resin foams are used, for example, as heat insulating materials for structures. In recent years, there has been an increasing demand for energy saving in houses and buildings, and there is a demand for technological development of foams with higher heat insulating properties than ever before.

[0004] Proposed methods for producing highly insulating foams include a production method in which graphite or titanium oxide is added in a prescribed range as a heat radiation inhibitor (see, for example, Patent Document 1), and a production method for extruded styrene resin foams that uses, as a foaming agent, environmentally friendly fluorinated olefins (hydrofluoroolefins and hydrochlorofluoroolefins) that have an ozone depletion potential of zero and a small global warming potential, or alkyl chlorides such as methyl chloride and ethyl chloride (see, for example, Patent Documents 2 to 4). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-221110 A [Patent Document 2] Special Publication No. 2008-546892 [Patent Document 3] JP 2019-189811 A [Patent Document 4] JP 2019-108416 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present inventors have newly discovered that when graphite is used as a material for an extruded styrene-based resin foam, adding the graphite in the form of a master batch may result in the generation of foreign matter.

[0007] Therefore, an object of the present invention is to provide a method for producing an extruded styrene resin foam, which can suppress the generation of foreign matter. [Means for solving the problem]

[0008] In order to solve the above problems, the present inventors have conducted intensive research and have found that the generation of foreign matter in a foam can be suppressed by adding a specific component to a graphite master batch, thereby completing the present invention. The present invention includes the following aspects. <1> A method for producing an extruded styrenic resin foam, comprising the step of melt-kneading a styrenic resin, a graphite masterbatch, and a foaming agent, wherein the graphite masterbatch contains graphite and a polyhydric alcohol fatty acid ester. <2> a ratio (MFRg / MFRr) of a melt mass flow rate (MFRg) of the graphite masterbatch measured under conditions of a test temperature of 200°C and a load of 5 kg according to Method A of JIS K7210-1 (2014) to a melt mass flow rate (MFRr) of the styrene-based resin measured under conditions of a test temperature of 200°C and a load of 5 kg according to Method A of JIS K7210-1 (2014) is 0.20 or more; <1> 2. A method for producing an extruded styrene-based resin foam according to claim 1 . <3> The polyhydric alcohol fatty acid ester is contained in an amount of 1.0% by weight or more based on 100% by weight of the graphite masterbatch. <1> or <2> 2. A method for producing an extruded styrene-based resin foam according to claim 1 . <4> The polyhydric alcohol fatty acid ester includes a glycerin fatty acid ester. <1> ~ <3> 13. The method for producing the extruded styrene resin foam according to claim 12. <5> The glycerol fatty acid ester is at least one selected from the group consisting of lauric acid monoglyceride, lauric acid diglyceride, lauric acid triglyceride, palmitic acid monoglyceride, palmitic acid diglyceride, palmitic acid triglyceride, stearic acid monoglyceride, stearic acid diglyceride, stearic acid triglyceride, and stearic acid tetraglyceride. <4> 2. A method for producing an extruded styrene-based resin foam according to claim 1 . <6> The graphite is contained in an amount of 40% by weight or more based on 100% by weight of the graphite masterbatch. <1> ~ <5> 13. The method for producing the extruded styrene resin foam according to claim 12. <7> a ratio (MFRg / MFRr) of a melt mass flow rate (MFRg) of the graphite masterbatch measured under conditions of a test temperature of 200°C and a load of 5 kg according to Method A of JIS K7210-1 (2014) to a melt mass flow rate (MFRr) of the styrene-based resin measured under conditions of a test temperature of 200°C and a load of 5 kg according to Method A of JIS K7210-1 (2014) is 0.50 or more, and the blowing agent contains an alkyl chloride. <1> ~ <6> 13. The method for producing the extruded styrene resin foam according to claim 12. <8> The thermal conductivity of the extruded styrene-based resin foam is 0.0244 W / mK or less. <1> ~ <7> 13. The method for producing the extruded styrene resin foam according to claim 12. <9> The apparent density of the extruded styrene resin foam is 20 to 60 kg / m 3 That is, <1> ~ <8> 13. The method for producing the extruded styrene resin foam according to claim 12. <10> The thickness of the styrene-based resin extruded foam is 10 mm or more and 150 mm or less. <1> ~ <9> 13. The method for producing the extruded styrene resin foam according to claim 12. Effect of the Invention

[0009] According to one embodiment of the present invention, generation of foreign matter in an extruded styrene-based resin foam is suppressed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims. The technical scope of the present invention also includes embodiments and examples obtained by appropriately combining the technical means disclosed in different embodiments and examples. In addition, all academic literature and patent documents described in this specification are incorporated herein by reference. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more and B or less."

[0011] [1. Extruded styrene resin foam] A method for producing an extruded styrenic resin foam according to one embodiment of the present invention comprises a step of adding a foaming agent to a melt of a graphite-containing styrenic resin composition to prepare a foamable molten material, and is characterized in that a graphite masterbatch containing graphite and a polyhydric alcohol fatty acid ester is used.

[0012] Generally, graphite is added in the form of a master batch in order to facilitate mixing of graphite into molten resin. However, when graphite is used as a material for a styrene-based resin extruded foam and the graphite is added in the form of a master batch, foreign matter may be generated in the styrene-based resin extruded foam depending on the type and blending of components such as the styrene-based resin and the blowing agent. The present inventors investigated and analyzed the foreign matter, and found that the foreign matter originates from the graphite master batch. As a result of the study by the present inventors, by including a polyhydric alcohol fatty acid ester in the graphite master batch, the generation of foreign matter in the styrene-based resin extruded foam can be stably suppressed regardless of the type and blending of components such as the styrene-based resin and the blowing agent. This is presumably because the MFR of the graphite master batch is adjusted by including a polyhydric alcohol fatty acid ester in the graphite master batch, and the MFR of the styrene-based resin and the graphite master batch are properly balanced, thereby improving the mixability of the styrene-based resin and the graphite master batch and suppressing the remaining of unmelted matter.

[0013] (1-1. Styrene-based resin) In one embodiment of the present invention, the styrene-based resin extrusion foam uses a styrene-based resin as a base resin. The styrene-based resin used in one embodiment of the present invention is not particularly limited, and examples thereof include (i) homopolymers of styrene-based monomers such as styrene, methylstyrene, ethylstyrene, isopropylstyrene, dimethylstyrene, bromostyrene, chlorostyrene, vinyltoluene, and vinylxylene, or copolymers consisting of a combination of two or more monomers, and (ii) copolymers obtained by copolymerizing the styrene-based monomer with one or more copolymerizable other monomers such as divinylbenzene, butadiene, acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, acrylonitrile, maleic anhydride, and itaconic anhydride. The other copolymerizable monomer can be used in an amount that does not reduce the physical properties such as the compressive strength of the styrene-based resin extrusion foam to be produced. In addition, the styrene-based resin used in one embodiment of the present invention is not limited to the homopolymer or copolymer of the styrene-based monomer, and may be a blend of the homopolymer or copolymer of the styrene-based monomer and the homopolymer or copolymer of the other monomer. For example, the styrene-based resin used in one embodiment of the present invention may be a blend of a homopolymer or copolymer of the styrene-based monomer and a diene-based rubber-reinforced polystyrene or an acrylic rubber-reinforced polystyrene. Furthermore, the styrene-based resin used in one embodiment of the present invention may be a styrene-based resin having a branched structure for the purpose of adjusting MFR, melt viscosity during molding, melt tension, etc. These may be used alone, or two or more types different in copolymerization components, molecular weights, molecular weight distributions, branched structures, and / or MFRs may be mixed and used.

[0014] In one embodiment of the present invention, it is preferable to use a styrene-based resin having an MFR of 0.1 to 50 g / 10 min, because (i) it is excellent in molding processability during extrusion foaming, (ii) it is easy to adjust the discharge amount during molding, the thickness, width, apparent density, and closed cell ratio of the obtained styrene-based resin extruded foam to desired values, (iii) it is excellent in foamability (the thickness, width, apparent density, closed cell ratio, and surface properties of the foam are easily adjusted to desired conditions), (iv) it is possible to obtain an extruded styrene-based resin foam with excellent appearance, and (v) it is possible to obtain an extruded styrene-based resin foam with a good balance of properties (for example, mechanical strength such as compressive strength, bending strength, or bending deflection amount, toughness, etc.). Furthermore, the MFR of the styrene-based resin is more preferably 0.3 to 30 g / 10 min, and particularly preferably 0.5 to 25 g / 10 min, from the viewpoint of the balance between molding processability and foamability, and mechanical strength and toughness. However, it is preferable to determine the MFR of the styrene resin in relation to the MFR of the graphite master batch described later. In one embodiment of the present invention, the MFR is measured according to JIS K7210-1 (2014) Method A and test condition H (test temperature 200°C, load 5 kg).

[0015] (1-2. Graphite masterbatch) In one embodiment of the present invention, the extruded styrene-based resin foam uses graphite as a heat radiation inhibitor to improve heat insulation. Examples include scaly (flake) graphite, amorphous graphite, spherical graphite, and artificial graphite. Among these, it is preferable to use graphite whose main component is scaly (flake) graphite because of its high heat radiation inhibitory effect. The graphite preferably has a fixed carbon content of 80% or more, and more preferably 85% or more. By setting the fixed carbon content within the above range, a foam having high heat insulation properties can be obtained.

[0016] The average particle size of the graphite is preferably 15 μm or less, more preferably 10 μm or less. By setting the average particle size within the above range, the specific surface area of ​​the graphite increases, and the probability of collision with heat radiation increases, thereby enhancing the heat radiation suppression effect. The average particle size means the particle size at which the cumulative volume of the total particle volume is 50% (volume average particle size by laser diffraction scattering method) when the particle size distribution is measured and analyzed by a laser diffraction scattering method based on the Mie theory in accordance with ISO13320:2009 and JIS Z8825:2013.

[0017] In one embodiment of the present invention, the graphite is used in the form of a masterbatch. The graphite masterbatch is a resin in which graphite is dispersed at a high concentration. The graphite masterbatch is preferably prepared so that the styrene resin contains 30 to 70% by weight of graphite, and more preferably so that the styrene resin contains 40 to 60% by weight of graphite. As the styrene resin used in the graphite masterbatch, those exemplified in "1-1. Styrene-based resin" above can be used and are suitable. From the viewpoint of kneadability, the MFR of the styrene resin is preferably 0.5 to 30 g / min. From the viewpoint of kneadability with the base resin, the MFR of the graphite masterbatch is preferably 0.3 to 30 g / 10 min, and more preferably 0.5 to 25 g / 10 min. However, the MFR of the graphite masterbatch is preferably determined in relation to the MFR of the styrene resin as follows.

[0018] In one embodiment of the present invention, the ratio (MFRg / MFRr) of the melt mass flow rate (MFRg) of the graphite master batch measured under the conditions of a test temperature of 200° C. and a load of 5 kg according to the A method of JIS K7210-1 (2014) to the melt mass flow rate (MFRr) of the styrene resin measured under the conditions of a test temperature of 200° C. and a load of 5 kg according to the A method of JIS K7210-1 (2014) is preferably 0.20 or more and 5 or less, more preferably 0.21 or more and 4 or less, and even more preferably 0.22 or more and 3 or less. By setting the ratio value of the MFR of the base resin and the graphite master batch to a specific value, the generation of foreign matter can be effectively suppressed. In particular, in a form in which the foaming agent contains alkyl chloride, foreign matter tends to be generated easily, and when the ratio value (MFRg / MFRr) of the MFR is adjusted to 0.50 or more, it acts more effectively and the generation of foreign matter is suppressed.

[0019] In one embodiment of the present invention, in order to adjust the MFR of the graphite masterbatch, a polyhydric alcohol fatty acid ester is contained in the graphite masterbatch. Examples of the polyhydric alcohol fatty acid ester used in one embodiment of the present invention include esters of higher fatty acids having 10 to 24 carbon atoms and polyhydric alcohols such as ethylene glycol, glycerin, 1,2,4-butanetriol, diglycerin, pentaerythritol, sorbitol, erythritol, hexanetriol, etc. These polyhydric alcohol fatty acid esters may be used alone or in combination of two or more kinds.

[0020] Among these, glycerin fatty acid esters, particularly mono-, di-, tri- or tetra-fatty acid esters of glycerin are preferred from the standpoints of availability, cost, etc.

[0021] As the glycerol fatty acid ester, it is preferable to use at least one selected from the group consisting of, for example, lauric acid monoglyceride, lauric acid diglyceride, lauric acid triglyceride, palmitic acid monoglyceride, palmitic acid diglyceride, palmitic acid triglyceride, stearic acid monoglyceride, stearic acid diglyceride, stearic acid triglyceride, and stearic acid tetraglyceride. The amount of the polyhydric alcohol fatty acid ester used in one embodiment of the present invention is adjusted so that it is contained in the graphite masterbatch at 0.5 to 6.0% by weight, more preferably 1.0 to 5.0% by weight, and even more preferably 1.5 to 4.0% by weight. If the amount of the polyhydric alcohol fatty acid ester is less than 0.5% by weight, there is almost no effect in adjusting the MFR, and if it exceeds 6.0% by weight, the processability of the masterbatch decreases. In the method for producing an extruded styrene resin foam according to one embodiment of the present invention, graphite is used (added) in the form of a graphite masterbatch, but a part of the graphite may be added directly without being in the form of a masterbatch. Adding a part of the graphite directly may be economically advantageous in some cases.

[0022] The graphite content in the styrene-based resin extruded foam in one embodiment of the present invention is preferably 0.5 to 5.0 parts by weight, more preferably 1.0 to 3.0 parts by weight, based on 100 parts by weight of the resin component. If the content is less than 0.5 parts by weight, a sufficient heat radiation suppression effect cannot be obtained. If the content is more than 5.0 parts by weight, the heat radiation suppression effect corresponding to the content cannot be obtained, and there is no cost advantage. The "resin component" referred to here refers to the resin component including the base resin and the resin contained in the graphite master batch.

[0023] (1-3. Foaming Agent) In one embodiment of the present invention, examples of the foaming agent include hydrofluoroolefin and / or hydrochlorofluoroolefin (hereinafter, "hydrofluoroolefin and / or hydrochlorofluoroolefin" may be referred to as "hydro(chloro)fluoroolefin"). A saturated hydrocarbon having 3 to 5 carbon atoms, and other foaming agents are mentioned. From the viewpoint of improving the heat insulating properties of the extruded styrene-based resin foam, it is preferable to use a hydro(chloro)fluoroolefin as the foaming agent. These foaming agents may be used alone or in combination of two or more kinds. For example, a saturated hydrocarbon having 3 to 5 carbon atoms and a hydrofluoroolefin may be used in combination.

[0024] The hydrofluoroolefin used in one embodiment of the present invention is not particularly limited, but tetrafluoropropene and hexafluorobutene are preferred from the viewpoint of low gas thermal conductivity and safety.Specific examples include trans-1,3,3,3-tetrafluoropropene (trans-HFO-1234ze), cis-1,3,3,3-tetrafluoropropene (cis-HFO-1234ze), 2,3,3,3-tetrafluoropropene (trans-HFO-1234yf), and cis-1,1,1,4,4,4-hexafluoro-2-butene (cis-HFO-1336mzz).In addition, the hydrochlorofluoroolefin used in one embodiment of the present invention is not particularly limited, but hydrochlorotrifluoropropene is preferred from the viewpoint of low gas thermal conductivity and safety.Specific examples include trans-1-chloro-3,3,3-trifluoropropene (trans-HCFO-1233zd) and the like. These hydrofluoroolefins and hydrochlorofluoroolefins may be used alone or in combination of two or more kinds.

[0025] The amount of hydro(chloro)fluoroolefin added according to one embodiment of the present invention is preferably 1.0 to 14.0 parts by weight, more preferably 2.0 to 13.0 parts by weight, and particularly preferably 3.0 to 12.0 parts by weight, relative to 100 parts by weight of the resin component. When the amount of hydro(chloro)fluoroolefin added is less than 1.0 part by weight relative to 100 parts by weight of the resin component, the effect of improving the heat insulating property by hydro(chloro)fluoroolefin tends not to be expected. On the other hand, when the amount of hydro(chloro)fluoroolefin added is more than 14.0 parts by weight relative to 100 parts by weight of the resin component, the hydro(chloro)fluoroolefin separates from the resin melt during extrusion foaming, and spot holes (traces where a localized mass of hydro(chloro)fluoroolefin breaks through the surface of the extruded foam and is released into the outside air) are generated on the surface of the extruded foam, or the closed cell ratio is reduced, which may impair the heat insulating property.

[0026] Examples of the saturated hydrocarbon having 3 to 5 carbon atoms according to an embodiment of the present invention include propane, n-butane, i-butane, n-pentane, i-pentane, and neopentane. Among these saturated hydrocarbons having 3 to 5 carbon atoms, propane, n-butane, i-butane, or a mixture thereof is preferred from the viewpoint of foamability. Furthermore, from the viewpoint of heat insulating properties of the extruded styrene resin foam, n-butane, i-butane, or a mixture thereof is preferred, and i-butane is particularly preferred. Hereinafter, i-butane is also referred to as "isobutane".

[0027] Depending on the desired properties of the foam, such as the expansion ratio and flame retardancy, the amount of hydro(chloro)fluoroolefin and / or saturated hydrocarbon having 3 to 5 carbon atoms may be limited. If the amount is outside the desired range, the extrusion foam moldability may be insufficient. In this case, by further using another foaming agent, a plasticizing effect and / or a co-foaming effect during foam production can be obtained. This allows the extrusion pressure to be reduced, making it possible to stably produce foams.

[0028] In the present invention, further, by using another foaming agent, a plasticizing effect and / or a co-foaming effect during foam production can be obtained, the extrusion pressure can be reduced, and a foam can be stably produced.

[0029] Examples of other foaming agents include organic foaming agents such as ethers such as dimethyl ether, diethyl ether, methyl ethyl ether, isopropyl ether, n-butyl ether, diisopropyl ether, furan, furfural, 2-methylfuran, tetrahydrofuran, and tetrahydropyran; ketones such as dimethyl ketone, methyl ethyl ketone, diethyl ketone, methyl-n-propyl ketone, methyl-n-butyl ketone, methyl-i-butyl ketone, methyl-n-amyl ketone, methyl-n-hexyl ketone, ethyl-n-propyl ketone, and ethyl-n-butyl ketone; saturated alcohols having 1 to 4 carbon atoms such as methanol, ethanol, propyl alcohol, i-propyl alcohol, butyl alcohol, i-butyl alcohol, and t-butyl alcohol; carboxylates such as methyl formate, ethyl formate, propyl formate, butyl formate, amyl formate, methyl propionate, and ethyl propionate; and alkyl halides such as methyl chloride and ethyl chloride. In addition, inorganic foaming agents such as water and carbon dioxide, chemical foaming agents such as azo compounds and tetrazole, etc. can also be used. These other foaming agents can be used alone or in combination of two or more.

[0030] Among the other blowing agents, from the viewpoints of foaming property and foam moldability, etc., saturated alcohols having 1 to 4 carbon atoms, dimethyl ether, diethyl ether, methyl ethyl ether, methyl chloride, ethyl chloride, etc. are preferred. From the viewpoints of the combustibility of the blowing agent, the flame retardancy or heat insulating property of the foam, etc., water and carbon dioxide are preferred. Among these, dimethyl ether is particularly preferred from the viewpoint of the plasticizing effect. From the viewpoints of the cost and the effect of improving heat insulating property by controlling the bubble diameter, water is particularly preferred. The total amount of the foaming agent according to one embodiment of the present invention is preferably 2 to 20 parts by weight, more preferably 2 to 15 parts by weight, based on 100 parts by weight of the resin component. If the amount of the foaming agent is 2 parts by weight or more, the expansion ratio can be sufficiently increased, and the properties of the resin foam, such as light weight and heat insulating properties, can be easily exhibited. If the amount of the foaming agent is 20 parts by weight or less, the occurrence of defects such as voids in the foam can be prevented. In one embodiment of the present invention, when water is used as a foaming agent, it is preferable to add a water-absorbing substance in order to perform stable extrusion foam molding. Specific examples of the water-absorbing substance used in one embodiment of the present invention include water-absorbing polymers such as polyacrylate polymers, starch-acrylic acid graft copolymers, polyvinyl alcohol polymers, vinyl alcohol-acrylate copolymers, ethylene-vinyl alcohol copolymers, acrylonitrile-methyl methacrylate-butadiene copolymers, polyethylene oxide copolymers, and derivatives thereof, as well as fine powders having a particle size of 1000 nm or less and having hydroxyl groups on the surface, such as anhydrous silica (silicon oxide) having silanol groups on the surface [for example, AEROSIL manufactured by Nippon Aerosil Co., Ltd. is commercially available]; water-absorbing or water-swelling layered silicates such as smectite and swelling fluoromica, and their organically treated products; and porous substances such as zeolite, activated carbon, alumina, silica gel, porous glass, activated clay, diatomaceous earth, and bentonite. The amount of the water-absorbing substance added is appropriately adjusted depending on the amount of water added, but is preferably 0.01 to 5 parts by weight, and more preferably 0.1 to 3 parts by weight, per 100 parts by weight of the resin component.

[0031] (1-4. Flame retardants) In one embodiment of the present invention, a flame retardant is added to the extruded styrene-based resin foam, thereby imparting flame retardancy to the resulting extruded styrene-based resin foam.

[0032] As the flame retardant, a bromine-based flame retardant is preferably used. Specific examples of the bromine-based flame retardant in one embodiment of the present invention include hexabromocyclododecane, tetrabromobisphenol A-bis(2,3-dibromo-2-methylpropyl)ether, tetrabromobisphenol A-bis(2,3-dibromopropyl)ether, tris(2,3-dibromopropyl)isocyanurate, and aliphatic bromine-containing polymers such as brominated styrene-butadiene block copolymers. These may be used alone or in combination of two or more.

[0033] Among these, tetrabromobisphenol A-bis(2,3-dibromo-2-methylpropyl)ether, mixed brominated flame retardants consisting of tetrabromobisphenol A-bis(2,3-dibromopropyl)ether, brominated styrene-butadiene block copolymer, and hexabromocyclododecane are preferably used because they have good extrusion operation and do not adversely affect the heat resistance of the foam, etc. These substances may be used alone or as a mixture.

[0034] The content of the bromine-based flame retardant in the styrene-based resin extruded foam in one embodiment of the present invention is preferably 1.0 to 8.0 parts by weight, more preferably 1.5 to 7.0 parts by weight, and even more preferably 2.0 to 6.0 parts by weight, based on 100 parts by weight of the resin component. If the content of the bromine-based flame retardant is less than 1.0 part by weight, it is difficult to obtain good properties as a foam such as flame retardancy, while if it exceeds 8.0 parts by weight, the stability and surface properties during foam production may be impaired. However, it is more preferable that the content of the flame retardant is appropriately adjusted according to the amount of foaming agent added, the apparent density of the foam, and the type or content of additives having a flame retardant synergistic effect, so that the flame retardancy specified in JIS A 9521 Measurement Method A is obtained.

[0035] In one embodiment of the present invention, a radical generator can be used in combination with the styrene-based resin extrusion foam in order to improve the flame retardancy. Specific examples of the radical generator include 2,3-dimethyl-2,3-diphenylbutane, poly-1,4-diisopropylbenzene, 2,3-diethyl-2,3-diphenylbutane, 3,4-dimethyl-3,4-diphenylhexane, 3,4-diethyl-3,4-diphenylhexane, 2,4-diphenyl-4-methyl-1-pentene, and 2,4-diphenyl-4-ethyl-1-pentene. Peroxides such as dicumyl peroxide are also used. Among them, those stable under the resin processing temperature conditions are preferred, specifically 2,3-dimethyl-2,3-diphenylbutane and poly-1,4-diisopropylbenzene are preferred, and the preferred amount of the radical generator to be added is 0.05 to 0.5 parts by weight relative to 100 parts by weight of the resin component.

[0036] Furthermore, for the purpose of improving flame retardancy, in other words as a flame retardant auxiliary, phosphorus-based flame retardants such as phosphate esters and phosphine oxides can be used in combination within a range that does not impair thermal stability. Examples of phosphate esters include triphenyl phosphate, tris(tributylbromoneopentyl)phosphate, tricresyl phosphate, trixylyleneyl phosphate, cresyl diphenyl phosphate, 2-ethylhexyl diphenyl phosphate, trimethyl phosphate, triethyl phosphate, tributyl phosphate, tris(2-ethylhexyl)phosphate, tris(butoxyethyl)phosphate, and condensed phosphate esters, and triphenyl phosphate and tris(tributylbromoneopentyl)phosphate are particularly preferred. In addition, triphenylphosphine oxide is preferred as a phosphine oxide-type phosphorus-based flame retardant. These phosphate esters and phosphine oxides may be used alone or in combination of two or more. The preferred amount of the phosphorus-based flame retardant to be added is 0.1 to 2 parts by weight based on 100 parts by weight of the styrene-based resin.

[0037] (1-5. Stabilizers) In one embodiment of the present invention, a stabilizer for a flame retardant can be used. Specific examples of the stabilizer include, but are not limited to, (i) epoxy compounds such as bisphenol A diglycidyl ether type epoxy resin, cresol novolac type epoxy resin, and phenol novolac type epoxy resin, (ii) polyhydric alcohol esters, which are reaction products of polyhydric alcohols such as pentaerythritol, dipentaerythritol, and tripentaerythritol with monovalent carboxylic acids such as acetic acid and propionic acid, or divalent carboxylic acids such as adipic acid and glutamic acid, and which are mixtures of esters having one or more hydroxyl groups in the molecule and may contain a small amount of the raw material polyhydric alcohol, and (iii) triethylene glycol-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, pentaerythritol tetrakis[3-( (iv) phosphite-based stabilizers such as 3,9-bis(2,4-di-tert-butylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane, and tetrakis(2,4-di-tert-butyl-5-methylphenyl)-4,4'-biphenylene diphosphonite), and the like are preferably used since they do not deteriorate the flame retardant performance of the foam and improve the thermal stability of the foam.

[0038] (1-6. Heat radiation suppressants) In one embodiment of the present invention, in addition to graphite, other heat radiation inhibitors may be used in combination. The heat radiation inhibitor refers to a substance that has the properties of reflecting, scattering, and absorbing light in the near infrared or infrared region. By containing a heat radiation inhibitor, a foam having high heat insulation properties can be obtained. In addition to graphite, white particles such as titanium oxide, barium sulfate, zinc oxide, aluminum oxide, and antimony oxide can be used as heat radiation inhibitors that can be used in the present invention. These may be used alone or in combination of two or more. Among the white particles, titanium oxide or barium sulfate is preferred from the viewpoint of a large radiation suppression effect, and titanium oxide is more preferred. The average particle size of the white particles is not particularly limited, but in consideration of effectively reflecting infrared rays and coloring to resin, for example, titanium oxide is preferably 0.1 μm to 10 μm, and more preferably 0.15 μm to 5 μm.

[0039] The content of the white particles in the styrene-based resin extrusion foam in one embodiment of the present invention is preferably 1.0 parts by weight or more and 3.0 parts by weight or less, more preferably 1.5 parts by weight or more and 2.5 parts by weight or less, based on 100 parts by weight of the resin component. The white particles have a smaller heat radiation suppression effect than graphite, and when the content of the white particles is less than 1.0 part by weight, the white particles hardly have a heat radiation suppression effect even if they are contained. When the content of the white particles is more than 3.0 parts by weight, the heat radiation suppression effect corresponding to the content cannot be obtained, while the flame retardancy of the foam tends to deteriorate.

[0040] The total content of the heat radiation inhibitor in the styrene-based resin extrusion foam in one embodiment of the present invention is preferably 1.0 parts by weight or more and 6.0 parts by weight or less, more preferably 2.0 parts by weight or more and 5.0 parts by weight or less, based on 100 parts by weight of the resin component resin. When the total content of the heat radiation inhibitor is less than 1.0 part by weight, it is difficult to obtain heat insulation, while the content of the solid additive such as the heat radiation inhibitor increases, so that the number of nucleation points increases, so that the bubbles of the foam become finer, and the elongation of the resin itself deteriorates, which tends to make it difficult to give the extrusion foam a beautiful surface and to make the extrusion foam thick. However, when the total content of the heat radiation inhibitor exceeds 6.0 parts by weight, it tends to be inferior in particular in giving the extrusion foam a beautiful surface and making the extrusion foam thick, and further, the extrusion stability tends to be impaired, and the flame retardancy tends to be impaired.

[0041] (1-7. Moldability improver) In one embodiment of the present invention, a polyhydric alcohol fatty acid ester and / or polyethylene glycol may be added as a moldability improver, if necessary. The use of these can impart a beautiful surface to the extruded foam and increase the thickness of the extruded foam (i.e., improve the moldability of the extruded foam).

[0042] Examples of the polyhydric alcohol fatty acid ester used in one embodiment of the present invention include esters of higher fatty acids having 10 to 24 carbon atoms and polyhydric alcohols such as ethylene glycol, glycerin, 1,2,4-butanetriol, diglycerin, pentaerythritol, sorbitol, erythritol, hexanetriol, etc. These polyhydric alcohol fatty acid esters may be used alone or in combination of two or more kinds.

[0043] Among these, glycerin fatty acid esters, particularly mono-, di-, tri- or tetra-fatty acid esters of glycerin are preferred from the standpoints of availability, cost, etc.

[0044] As the glycerol fatty acid ester, it is preferable to use at least one selected from the group consisting of, for example, lauric acid monoglyceride, lauric acid diglyceride, lauric acid triglyceride, palmitic acid monoglyceride, palmitic acid diglyceride, palmitic acid triglyceride, stearic acid monoglyceride, stearic acid diglyceride, stearic acid triglyceride, and stearic acid tetraglyceride.

[0045] The melting point of the glycerin fatty acid ester used in the present invention is preferably 150° C. or less, more preferably 130° C. or less, and particularly preferably 110° C. When the melting point of the glycerin fatty acid ester is 150° C. or less, it is excellent in handleability, for example, in a dry blending step during the production of an extruded foam, and since it exists as a liquid during extrusion foam molding, it can also impart a plasticizing effect to the styrene-based resin during extrusion foam molding, so that it can exhibit a sufficient thickening effect of the extruded styrene-based resin foam. On the other hand, when the melting point is higher than 150° C., it exists as a solid during extrusion foam molding, and it cannot impart a plasticizing effect to the styrene-based resin during extrusion foam molding, so that it may not be possible to exhibit a sufficient thickening effect of the extruded styrene-based resin foam.

[0046] The amount of polyhydric alcohol fatty acid ester added in the method for producing a styrene-based resin extruded foam according to one embodiment of the present invention is preferably 0.05 parts by weight or more and 5.0 parts by weight or less, more preferably 0.1 parts by weight or more and 3.0 parts by weight or less, and particularly preferably 0.5 parts by weight or more and less than 2.0 parts by weight, relative to 100 parts by weight of the resin component. If the amount of polyhydric alcohol fatty acid ester added is less than 0.05 parts by weight, the effect of thickening the extruded foam tends to be insufficient. On the other hand, if the amount exceeds 5.0 parts by weight, the excessive amount may impair extrusion, foaming, and molding stability during production, or may deteriorate various properties such as heat resistance of the extruded foam.

[0047] The average molecular weight of the polyethylene glycol used in one embodiment of the present invention is not particularly limited, but is preferably from 1000 to 25000, more preferably from 1500 to 20000, and particularly preferably from 3000 to 15000. These polyethylene glycols having different average molecular weights may be used alone or in combination of two or more. When the molecular weight of the polyethylene glycol is from 1000 to 25000, the freezing point of the polyethylene glycol is higher than room temperature and the polyethylene glycol is in a solid state at room temperature, so that depending on the amount used, the polyethylene glycol has excellent handleability in, for example, a dry blending step during the production of an extruded foam, does not bleed out from the inside of the extruded foam to the surface, and has a freezing point lower than the extrusion foaming temperature, and can impart a plasticizing effect to the styrene-based resin during extrusion foaming, so that the polyethylene glycol can exert a sufficient effect of imparting surface properties to the styrene-based resin extruded foam and a sufficient effect of adding thickness.

[0048] The amount of polyethylene glycol added in one embodiment of the present invention is preferably 0.05 parts by weight or more and 5.0 parts by weight or less, more preferably 0.1 parts by weight or more and 3.0 parts by weight or less, and particularly preferably 0.2 parts by weight or more and 1.0 parts by weight or less, relative to 100 parts by weight of the styrene-based resin. If the amount of polyethylene glycol added is less than 0.05 parts by weight, the surface property imparting effect and the thickness-imparting effect tend to be insufficient. On the other hand, if the amount of polyethylene glycol added is more than 5.0 parts by weight, the amount of polyethylene glycol added is excessive, which may impair extrudability, foamability, and molding stability during production, or may deteriorate various properties such as the heat resistance of the extruded foam.

[0049] In one embodiment of the present invention, when polyethylene glycol and polyhydric alcohol fatty acid ester are used in combination as a moldability improving agent, the total amount of polyethylene glycol and polyhydric alcohol fatty acid ester is preferably 0.05 parts by weight or more and 5.0 parts by weight or less, more preferably 0.1 parts by weight or more and 3.0 parts by weight or less, and particularly preferably 0.2 parts by weight or more and 2.0 parts by weight or less, relative to 100 parts by weight of the resin component. If the content is less than 0.05 parts by weight, the surface property imparting effect and the thickness-imparting effect tend to be insufficient. On the other hand, if the content is more than 5.0 parts by weight, the content is excessive, which may impair extrudability, foamability, and molding stability during production, or may deteriorate various properties such as the heat resistance of the extruded foam.

[0050] (1-8. Other additives) In one embodiment of the present invention, further, as necessary, additives such as inorganic compounds such as silica, calcium silicate, wollastonite, kaolin, clay, mica, calcium carbonate, sodium stearate, calcium stearate, magnesium stearate, barium stearate, liquid paraffin, olefin wax, stearylamide compounds, phenol antioxidants, phosphorus stabilizers, nitrogen stabilizers, sulfur stabilizers, light resistance stabilizers such as benzotriazoles and hindered amines, cell size regulators such as talc, flame retardants other than the above, antistatic agents, colorants such as pigments, and plasticizers may be contained in the styrene resin, as long as the effect of one embodiment of the present invention is not impaired. In addition, as necessary, other resins may be used in combination with the styrene resin in the base resin, as long as the effect of one embodiment of the present invention is not impaired.

[0051] (1-9. Physical Properties) The thermal conductivity of the styrene-based resin extruded foam according to one embodiment of the present invention is not particularly limited, but from the viewpoint of thermal insulation considering that the foam functions, for example, as a thermal insulation material for building, or as a thermal insulation material for refrigerators or refrigerated vehicles, the thermal conductivity measured at an average temperature of 23°C one week after production is preferably 0.0284 W / mK or less, more preferably 0.0244 W / mK or less, and particularly preferably 0.0224 W / mK or less.

[0052] The apparent density of the extruded styrene-based resin foam according to one embodiment of the present invention is, for example, 20 kg / m from the viewpoint of heat insulation and light weight in consideration of its function as a heat insulating material for buildings, or a heat insulating material for refrigerators or refrigerated vehicles. 3 More than 60kg / m 3 It is preferably equal to or less than 25 kg / m 3 More than 40kg / m 3 The following is the result. The thickness of the styrene-based resin extruded foam according to one embodiment of the present invention is preferably 10 mm or more and 150 mm or less, and more preferably 15 mm or more and 120 mm or less, from the viewpoints of insulation properties and light weight, taking into consideration that the foam functions as, for example, an insulation material for building, or an insulation material for refrigerators or refrigerated vehicles.

[0053] The closed cell ratio of the extruded styrene-based resin foam according to one embodiment of the present invention is preferably 90% or more, more preferably 95% or more. If the closed cell ratio is less than 90%, the foaming agent will dissipate from the extruded foam early, resulting in a decrease in heat insulation.

[0054] The average bubble diameter in the thickness direction of the styrene-based resin extruded foam according to one embodiment of the present invention is preferably 0.05 mm or more and 0.5 mm or less, more preferably 0.05 mm or more and 0.4 mm or less, and particularly preferably 0.05 mm or more and 0.3 mm or less. In general, the smaller the average bubble diameter, the shorter the distance between the bubble walls of the foam, so that the range of movement of the bubbles of the extruded foam when shaping the extruded foam during extrusion foaming is narrow, making deformation difficult, and it tends to be difficult to impart a beautiful surface to the extruded foam and to produce a thickness of the extruded foam. When the average bubble diameter in the thickness direction of the styrene-based resin extruded foam is smaller than 0.05 mm, it becomes particularly difficult to impart a beautiful surface to the extruded foam and to produce a thickness of the extruded foam. On the other hand, when the average bubble diameter in the thickness direction of the styrene-based resin extruded foam exceeds 0.5 mm, there is a risk that sufficient heat insulation cannot be obtained.

[0055] The average cell diameter of the extruded styrene resin foam according to one embodiment of the present invention can be evaluated as follows using a microscope (DIGITAL MICROSCOPE VHX-900, manufactured by KEYENCE CORPORATION).

[0056] The obtained styrene-based resin extruded foam was observed from the extrusion direction at a widthwise center and at a location 150 mm from one end in the widthwise direction to the opposite end (the same location for both ends in the widthwise direction) at three locations in total at the center in the thickness direction, using the microscope, and a 100x magnified photograph was taken. Similarly, the extrusion direction vertical cross sections at the center in the thickness direction at three locations in the width direction were observed from the width direction using the microscope, and a 100x magnified photograph was taken. Three 2 mm straight lines were drawn arbitrarily in the thickness direction of the magnified photograph (three lines for each observation location and each observation direction), and the number a of bubbles in contact with the straight lines was measured. From the measured number a of bubbles, the average bubble diameter A in the thickness direction for each observation location was calculated by the following formula (1). The average value of the three locations (two directions at each location) was taken as the average bubble diameter A (average value) in the thickness direction of the styrene-based resin extruded foam.

[0057] Average bubble diameter A (mm) in the thickness direction at each observation point = 2 × 3 / number of bubbles a ···(1).

[0058] The cross sections perpendicular to the extrusion direction of the obtained styrene-based resin extruded foam at the center in the width direction and at a location 150 mm from one end in the width direction to the opposite end (the same location for both ends in the width direction) were observed from the width direction using the microscope, and 100x magnified photographs were taken. Three 2 mm straight lines were drawn in the extrusion direction of the enlarged photograph (three lines for each observation location), and the number b of bubbles in contact with the straight lines was measured. From the measured number b of bubbles, the average bubble diameter B in the extrusion direction for each observation location was calculated using the following formula (2). The average value of the three locations was taken as the average bubble diameter B (average value) in the extrusion direction of the styrene-based resin extruded foam.

[0059] Average bubble diameter in the extrusion direction at each observation point B (mm) = 2 × 3 / number of bubbles b (2).

[0060] The obtained styrene-based resin extruded foam was observed from the extrusion direction at a total of three locations, namely, the widthwise center and a location 150 mm from one end in the widthwise direction to the opposite end (the same location for both ends in the widthwise direction), in a widthwise vertical cross section, and a 100x magnified photograph was taken. Three 2 mm straight lines were drawn at random in the widthwise direction of the enlarged photograph (three lines for each observation location), and the number c of bubbles in contact with the straight lines was measured. From the measured number c of bubbles, the average cell diameter C in the width direction for each observation location was calculated by the following formula (3). The average value of the three locations was taken as the average cell diameter C (average value) in the width direction of the styrene-based resin extruded foam.

[0061] Average bubble diameter C (mm) in the width direction at each observation point = 2 × 3 / number of bubbles c (3).

[0062] The cell deformation ratio of the extruded styrene-based resin foam according to one embodiment of the present invention is preferably 0.7 to 2.0, more preferably 0.8 to 1.5, and even more preferably 0.8 to 1.2. If the cell deformation ratio is less than 0.7, the compressive strength is low, and the extruded foam may not have a strength suitable for the intended use. In addition, the cells tend to return to a spherical shape, and the extruded foam tends to have poor dimensional (shape) retention. On the other hand, if the cell deformation ratio exceeds 2.0, the number of cells in the thickness direction of the extruded foam is reduced, and the effect of improving the heat insulation due to the cell shape is reduced.

[0063] The cell deformation ratio of the extruded styrene resin foam according to one embodiment of the present invention can be calculated from the above-mentioned average cell diameter by the following formula (4).

[0064] Bubble deformation rate (unitless) = A (average value) / {〔B (average value) + C (average value)〕 / 2} (4).

[0065] The thickness of the styrene-based resin extruded foam according to one embodiment of the present invention is preferably from 10 mm to 150 mm, more preferably from 20 mm to 130 mm, and particularly preferably from 30 mm to 120 mm, from the viewpoints of thermal insulation, bending strength, and compressive strength in consideration of its function as, for example, a thermal insulation material for buildings, or a thermal insulation material for refrigerators or refrigerated vehicles.

[0066] As described in the examples and comparative examples of the present invention, in the case of an extruded styrene resin foam, after it is shaped by extrusion foaming, both surfaces of a plane perpendicular to the thickness direction may be cut to a depth of about 5 mm on each side in the thickness direction to obtain the product thickness. However, unless otherwise specified, the thickness of the extruded styrene resin foam according to one embodiment of the present invention refers to the uncut thickness after it has been shaped by extrusion foaming.

[0067] Thus, according to one embodiment of the present invention, it is possible to easily obtain an extruded styrene-based resin foam having excellent heat insulating properties and flame retardancy, a beautiful appearance, and a sufficient thickness suitable for use.

[0068] 2. Method for producing extruded styrene resin foam The configuration already explained in [1. Extruded styrene resin foam] is used by reference, and the explanation thereof will be omitted here.

[0069] As an example of a method for producing a styrene-based resin extrusion foam, the following method can be mentioned. First, a styrene-based resin and, if necessary, the various additives described above are supplied to a heat-melting section of an extruder having a die slit section (in other words, the resin composition is supplied to the heat-melting section of the extruder). At this time, a foaming agent can be mixed into the resin composition under high pressure conditions at any stage (for example, during or after the resin composition is heated and melted). This is the melting process.

[0070] Thereafter, the foamable molten material obtained in the melting step is cooled to a temperature suitable for extrusion foaming, and then the fluid gel is extruded through the die slit into a low pressure region (e.g., an atmospheric pressure region) for foaming, thereby forming an extruded styrene resin foam.

[0071] In the melting step, examples of the method of blending various additives with the styrene-based resin include a method of adding various additives to the styrene-based resin and mixing them by dry blending; a method of adding various additives to the molten styrene-based resin from a supply section provided in the middle of the extruder; a method of preparing a master batch in which various additives are incorporated into the styrene-based resin at a high concentration using an extruder, kneader, Banbury mixer, rolls, etc., and mixing the master batch with the styrene-based resin by dry blending; a method of feeding various additives to the extruder using a feed facility separate from the styrene-based resin, etc. However, in the present invention, graphite is added as a master batch.

[0072] The heating temperature in the heat melting section is equal to or higher than the temperature at which the styrene resin used melts. The heating temperature is preferably a temperature (for example, about 150°C to 260°C) at which molecular deterioration of the resin due to the influence of additives and the like is suppressed as much as possible. The melt kneading time in the heat melting section cannot be uniquely defined because it varies depending on the extrusion amount of the styrene resin per unit time and / or the type of extruder used as the melt kneading section, and can be appropriately set as the time required for the styrene resin, the foaming agent, and the additives to be uniformly dispersed and mixed.

[0073] As the melt-kneading section, a mechanism used in normal extrusion foaming can be used without any particular limitation, and examples thereof include a screw-type extruder.

[0074] The pressure at which the foaming agent is added or injected is not particularly limited, and may be any pressure higher than the internal pressure of an extruder or the like.

[0075] In the foaming step, the method of extrusion foaming may be, for example, a method in which the above-mentioned fluid gel is released from a high pressure region to a low pressure region through a die slit portion having a straight slit shape used for extrusion molding. In this way, an extruded foam is obtained. Note that the shape of the die slit portion is not particularly limited, and various die slit portions in the technical field can be used.

[0076] The extruded styrene resin foam may be molded into a plate-like foam, i.e., an extruded foam plate. For example, the extruded foam obtained as described above can be molded into a plate-like foam having a large cross-sectional area by using a molding die installed in close contact with or in contact with a slit die and a molding roll installed adjacent to the downstream side of the molding die. The desired cross-sectional shape, surface properties, and quality of the foam can be obtained by adjusting the flow surface shape of the molding die and the die temperature. EXAMPLES

[0077] Examples of the present invention will be described below, but the present invention is not limited to these.

[0078] [Raw materials] The raw materials used in the examples and comparative examples are as follows.

[0079] Styrene-based resin Polystyrene A [PS Japan Co., Ltd., 680; MFR 7.0g / 10min] Polystyrene B [Toyo Styrene Co., Ltd., G120; MFR 21g / 10min] Polystyrene C [PS Japan Co., Ltd., G9401; MFR 2.1g / 10min] Styrene-acrylonitrile copolymer [Denka AS GR-AT-5S, manufactured by Denka Co., Ltd.; acrylonitrile content 25% by weight, MFR 8.0g / 10min] Heat radiation suppressant Graphite [Marutoyo Foundry Manufacturing Co., Ltd., M-885; flake graphite, average particle size 5.5 μm, fixed carbon content 89%] ○Flame retardants Mixture of tetrabromobisphenol A bis(2,3-dibromo-2-methylpropyl) ether and tetrabromobisphenol A bis(2,3-dibromopropyl) ether as brominated flame retardants [GR-125P, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.] Flame retardant assistant ·Triphenylphosphine oxide [Sumitomo Corporation Chemicals] Stabilizers Bisphenol-A glycidyl ether [ADEKA Corporation, EP-13] Dipentaerythritol-adipic acid reaction mixture [Ajinomoto Fine-Techno Co., Ltd., Plain Riser ST210] Triethylene glycol-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate [Songwon Japan, Sonnox 2450FF] Other additives Talc [Talc Powder PK-Z, manufactured by Hayashi Kasei Co., Ltd.] Calcium stearate [Sakai Chemical Industry Co., Ltd., SC-P] Bentonite [Hojun Co., Ltd., Bengelbright 11K] Silica [Evonik Degussa Japan Co., Ltd., Carplex BS-304F] Stearic acid monoglyceride [Riken Vitamin Co., Ltd., Rikemal S-100P] Ethylene bis stearic acid amide [NOF Corp., Alflow H-50S] ○Foaming agent · HFO-1234ze [Honeywell Japan Co., Ltd.] Dimethyl ether [Iwatani Corporation] Ethyl chloride [Nippon Specialty Chemical Industry Co., Ltd.] Isobutane [Mitsui Chemicals, Inc.] Water [Settsu City, Osaka Prefecture tap water]

[0080] [Measurement method] In the examples and comparative examples, various parameters were measured and evaluated according to the following measurement methods.

[0081] (1) MFR of styrene resin and graphite masterbatch The MFR of the raw material styrene resin and the obtained graphite master batch was measured using a semi-automatic melt tester [Yasuda Seiki Seisakusho Co., Ltd., 120HA] in accordance with JIS K7210-1 (2014) Method A (test temperature 200°C, load 5.00 kg).

[0082] (2) Thickness of styrene-based resin extruded foam (before cutting) The thickness of the extruded foam plate with a cross section of 60 mm thick x 1000 mm wide obtained in [Preparation of extruded foam] described later was measured at three points in total, namely, the center in the width direction and a point 150 mm from one end in the width direction to the opposite end (the same point on both ends in the width direction), using a vernier caliper [Mitutoyo Corporation, M-type standard vernier caliper N30]. The average value of the three points was regarded as the thickness of the extruded styrene resin foam.

[0083] (3) Apparent density (kg / m 3 ) The weight of the resulting extruded styrene resin foam was measured, and its length (in the extrusion direction), width and thickness were also measured.

[0084] From the measured weight and each dimension, the apparent density of the extruded styrene resin foam was calculated based on the following formula. The unit of apparent density was then expressed as kg / m 3 was converted to. Apparent density (g / cm 3 ) = foam weight (g) / foam volume (cm 3 ).

[0085] (4) Closed cell ratio Test pieces measuring 40 mm thick, 25 mm long (in the extrusion direction), and 25 mm wide were cut out from three locations of the obtained extruded styrene foam: the widthwise center, a location 150 mm from one end in the widthwise direction toward the opposite end, and a location 150 mm from the other end in the widthwise direction toward the opposite end. The test pieces were measured according to procedure C of ASTM-D2856-70, and the closed cell ratio of each test piece was calculated by the following formula. The average value of the closed cell ratios at the three locations was taken as the closed cell ratio of the extruded styrene foam. Closed cell ratio (%)=(V1-W / ρ)×100 / (V2-W / ρ) Here, V1(cm 3 ) is the true volume of the test piece (excluding the volume of the part that is not an independent bubble) measured using an air comparison type specific gravity meter [Tokyo Science Co., Ltd., air comparison type specific gravity meter, Model 1000]. V2 (cm 3 ) is the apparent volume calculated from the outer dimensions of the test piece measured using a vernier caliper [Mitutoyo Corporation, M-type standard vernier caliper N30]. W (g) is the total weight of the test piece. Also, ρ (g / cm 3 ) is the density of the styrene resin that constitutes the extruded foam, and is 1.05 (g / cm 3 ) was decided.

[0086] (5) Average bubble diameter and bubble deformation rate For the obtained extruded styrene resin foam, the average cell diameter was measured using a microscope [DIGITAL MICROSCOPE VHX-900, manufactured by KEYENCE CORPORATION] as described above, and the cell deformation rate was calculated from the measured average cell diameter.

[0087] (6) Thermal conductivity In accordance with JIS A 9521, a test piece of 50 mm thickness × 300 mm length (extrusion direction) × 300 mm width cut from a styrene-based resin extruded foam was used to measure thermal conductivity at an average temperature of 23°C using a thermal conductivity measuring device [Eiko Seiki Co., Ltd., HC-074]. Specifically, after the production of the styrene-based resin extruded foam, a test piece of the above dimensions was cut out, and the test piece was subjected to standard temperature condition class 3 (23°C ± 5°C) and standard humidity condition class 3 (50°C ± 5°C) specified in JIS K 7100. +20、-10After standing under the condition of 50°C (20°F) and 100°C (30°F) RH, the thermal conductivity of the extruded styrene-based resin foam was measured one week (7 days) after production.

[0088] (7) JIS flammability In accordance with JIS A 9521, test pieces with a thickness of 10 mm, length (in the extrusion direction) of 200 mm, and width of 25 mm were used to evaluate flammability according to the following criteria. The manufactured styrene-based resin extrusion foam was cut into test pieces with the above dimensions, and the test pieces were then subjected to 3-phase heating under standard temperature conditions (23°C ± 5°C) and standard humidity conditions (50°C ± 5°C) as specified in JIS K 7100. +20、-10 The styrenic resin extrusion foams were left to stand under conditions of 50°C (20°F) and 100°C (30°F) (RH). One week (7 days) after production of the extruded styrene foams, the test pieces were used to evaluate the flammability. ○: Meets the criteria of "flame goes out within 3 seconds, there is no residual fuel, and the fire does not burn beyond the flammability limit indicator line." ×: Does not meet the above criteria.

[0089] (8) Foreign matter A foam board with a thickness of 50 mm, width of 910 mm, and length (in the extrusion direction) of 1820 mm was cut out from the obtained styrene-based resin extrusion foam, and further cut into 30 test pieces with a thickness of 10 mm, width of 910 mm, and length of about 300 mm (in the extrusion direction). The surfaces of the test pieces were visually inspected and evaluated for foreign matter according to the following criteria. ○: No foreign matter (unfoamed area) with a diameter of 2 mm or more was observed ×: Foreign matter (unfoamed part) of φ2 mm or more is observed

[0090] [Examples and Comparative Examples] Example 1 [Preparation of graphite master batch] 48% by weight of polystyrene [680, MFR 7.0g / 10min, manufactured by PS Japan Co., Ltd.], 50% by weight of graphite [M-885, manufactured by Marutoyo Foundry Co., Ltd.], and 2.0% by weight of stearic acid monoglyceride [Rikemal S-100P, manufactured by Riken Vitamin Co., Ltd.] were charged into a Banbury mixer and mixed at 5 kgf / cm. 2The mixture was melt-kneaded for 20 minutes without heating or cooling under a load of 1.5 kg. The resin temperature was measured and found to be 190°C. The resin strands were fed to a ruder and extruded through a die with small holes attached to the tip at a discharge rate of 250 kg / hr. The resin strands were cooled and solidified in a water bath at 30°C, and then cut to obtain a masterbatch. The MFR of the graphite masterbatch obtained is shown in Table 1.

[0091] [Preparation of resin mixture] The materials shown in Table 1 (materials other than the foaming agent) were dry-blended in the composition shown in Table 1 to obtain a resin mixture.

[0092] [Preparation of extruded foam] The obtained resin composition was supplied at about 800 kg / hr to an extruder in which a single screw extruder (first extruder) with a diameter of 150 mm, a single screw extruder (second extruder) with a diameter of 200 mm, and a cooler were connected in series.

[0093] The resin composition fed to the first extruder was heated to 250° C. to melt or plasticize it, and kneaded to obtain a resin composition, and a foaming agent was injected into the resin composition near the tip of the first extruder.

[0094] The resin composition was then cooled to the resin temperature shown in Table 1 in the second extruder and cooler connected to the first extruder, and extruded into the atmosphere at the foaming pressure shown in Table 1 through a die (slit die) with a rectangular cross section and a thickness shown in Table 1, which was attached to the tip of the cooler, and then an extruded foam board with a cross section of 60 mm thick x 1000 mm wide was obtained using a molding die placed in close contact with the die and a molding roll placed downstream of it. The evaluation results of the obtained foam are shown in Table 1.

[0095] (Examples 2 to 6) A graphite masterbatch and an extruded foam were obtained in the same manner as in Example 1, except that the formulation and production conditions were changed as shown in Table 1. The physical properties of the obtained extruded foam are shown in Table 1.

[0096] (Comparative Examples 1 to 3) A graphite masterbatch and an extruded foam were obtained in the same manner as in Example 1, except that the formulation and production conditions were changed as shown in Table 2. The physical properties of the obtained extruded foam are shown in Table 2.

[0097] [Table 1]

[0098] [Table 2]

[0099] As shown in Table 1, no foreign matter was found in the foam in Examples 1 to 6. On the other hand, as shown in Table 2, foreign matter was found in Comparative Examples 1 to 3. [Industrial Applicability]

[0100] The extruded styrene-based resin foam according to one embodiment of the present invention can be used, for example, as a heat insulating material, a sound absorbing material, a core material for a vacuum heat insulating material, a cushioning material, and a filler material.

Claims

1. A method for producing an extruded styrene-based resin foam, comprising melt-kneading a styrene-based resin, a graphite master batch, and a foaming agent, the graphite masterbatch comprises graphite and a polyhydric alcohol fatty acid ester; The polyhydric alcohol fatty acid ester is contained in an amount of 0.5 to 6.0% by weight based on 100% by weight of the graphite masterbatch.

2. The method for producing an extruded styrene-based resin foam according to claim 1, wherein the ratio (MFRg / MFRr) of the melt mass flow rate (MFRg) of the graphite master batch measured under conditions of a test temperature of 200°C and a load of 5 kg according to a method A of JIS K7210-1 (2014) to the melt mass flow rate (MFRr) of the styrene-based resin measured under conditions of a test temperature of 200°C and a load of 5 kg according to a method A of JIS K7210-1 (2014) is 0.20 or more.

3. The method for producing an extruded styrene resin foam according to claim 1 or 2, wherein the polyhydric alcohol fatty acid ester comprises a glycerin fatty acid ester.

4. 4. The method for producing an extruded styrene resin foam according to claim 3, wherein the glycerol fatty acid ester is at least one selected from the group consisting of lauric acid monoglyceride, lauric acid diglyceride, lauric acid triglyceride, palmitic acid monoglyceride, palmitic acid diglyceride, palmitic acid triglyceride, stearic acid monoglyceride, stearic acid diglyceride, and stearic acid triglyceride.

5. The method for producing an extruded styrene resin foam according to any one of claims 1 to 4, wherein the graphite is contained in an amount of 40% by weight or more based on 100% by weight of the graphite masterbatch.

6. a ratio (MFRg / MFRr) of a melt mass flow rate (MFRg) of the graphite masterbatch measured under conditions of a test temperature of 200° C. and a load of 5 kg in accordance with Method A of JIS K7210-1 (2014) to a melt mass flow rate (MFRr) of the styrene-based resin measured under conditions of a test temperature of 200° C. and a load of 5 kg in accordance with Method A of JIS K7210-1 (2014) is 0.50 or more, The method for producing an extruded styrene resin foam according to any one of claims 1 to 5, wherein the foaming agent contains an alkyl chloride.

7. The method for producing an extruded styrene-based resin foam according to any one of claims 1 to 6, wherein the extruded styrene-based resin foam has a thermal conductivity of 0.0244 W / mK or less.

8. The apparent density of the styrene-based resin extruded foam is 20 to 60 kg / m 3 The method for producing an extruded styrene resin foam according to any one of claims 1 to 7.

9. The method for producing an extruded styrene resin foam according to any one of claims 1 to 8, wherein the extruded styrene resin foam has a thickness of 10 mm or more and 150 mm or less.

Citation Information

Patent Citations

  • Production of master batch for packing material for photographic sensitized material and production of molding resin using the same master batch

    JP1992342730A

  • Foaming agents and compositions containing fluorinated olefins, and foaming methods

    JP2008546892A

  • Extruded styrene resin foam and method for producing the same

    JP2013221110A

  • Method for producing styrenic resin extruded foamed body

    JP2018184563A

  • Styrenic resin extrusion foamed body and manufacturing method thereof

    JP2019108416A